Effects of group mindfulness intervention on high-level distance runners: a quasi-experimental study - Kelemen, B.; Tóth, R.; Benczenleitner, O.; Tóth, L. (Frontiers in Sports and Active Living, 2025)
Introduction: Player profiling is fundamental to effective talent identification and development strategies. However, whilst anthropometric and physiological profiling is customary practice, effective evaluation of technical and tactical skills in team sports has arguable been overlooked, largely due to a lack of suitable measurement tools. Therefore, the aim of the present study was to design, validate, and test the reliability of a novel observational instrument for assessing technical and tactical skills in rugby union.